Semantic shift of crisis neologisms in digital media: a sociolinguistic study - Mella Narolita (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study provides a sociolinguistic analysis of how crisis neologisms reconfigure their meanings in response to structural societal stress. Utilizing a descriptive qualitative method and Geoffrey Leech’s framework of seven types of meaning, this research investigates five prominent terms: burnout, quiet quitting, job hugging, hustle culture, and underconsumption. By analyzing linguistic data extracted from the News on the Web (NOW) Corpus, this study offers empirical evidence of significant semantic migration across the entire sample set. The findings reveal that these neologisms do not remain static; rather, they shift beyond their original conceptual definitions into affective, collocative, and connotative realms to reflect modern pressures such as labor instability, mental health crises, and changing consumption patterns. This research contributes a novel framework for digital lexicography, offering practical applications for media analysts and communication experts to better identify, decode, and interpret the linguistic indicators of emergent societal tensions.